2018
DOI: 10.1002/ange.201802446
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Aqueous Late‐Stage Radiolabelling of [GaF3(BnMe2‐tacn)] by 18F/19F Isotopic Exchange: Towards New PET Imaging Probes

Abstract: A simple and rapid method for 18F radiolabelling of [GaF3(BnMe2‐tacn)] by 18F/19F isotopic exchange is described. The use of MeCN/H2O or EtOH/H2O (75:25) and aqueous [18F]F− (up to 200 MBq) with heating (80 °C, 10 min) gave 66±4 % 18F incorporation at a concentration of 268 nm, and 37±5 % 18F incorporation at even lower concentration (27 nm), without the need for a Lewis acid promoter. A solid‐phase extraction method was established to give [Ga18F19F2(BnMe2‐tacn)] in 99 % radiochemical purity in an EtOH/H2O mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Comparatively, when GaCl was complexed to a NODA chelator, the same results could be achieved in only 30 min at room temperature without the addition of an organic co-solvent ( Bhalla et al, 2015 ). [ 18 F]GaF 3 (BnMe 2 -tacn) has also be synthesized through 19 F/ 18 F isotopic exchange, however, it was performed in 25% water and required heating to 80°C ( Monzittu et al, 2018 ). Reid et al have also reported the radiolabeling of AlCl 3 (BnMe 2 -tacn) using McBride’s method (pH 4.0, 100°C) with carrier added [ 18 F]KF that lead to a RCY of 24% in 60–90 min ( Levason et al, 2017 ).…”
Section: Strategies For Directly Radiolabeling Peptides and Proteins With Through Heteroatom-and Metal-[ 18 F]fluoridementioning
confidence: 99%
“…Comparatively, when GaCl was complexed to a NODA chelator, the same results could be achieved in only 30 min at room temperature without the addition of an organic co-solvent ( Bhalla et al, 2015 ). [ 18 F]GaF 3 (BnMe 2 -tacn) has also be synthesized through 19 F/ 18 F isotopic exchange, however, it was performed in 25% water and required heating to 80°C ( Monzittu et al, 2018 ). Reid et al have also reported the radiolabeling of AlCl 3 (BnMe 2 -tacn) using McBride’s method (pH 4.0, 100°C) with carrier added [ 18 F]KF that lead to a RCY of 24% in 60–90 min ( Levason et al, 2017 ).…”
Section: Strategies For Directly Radiolabeling Peptides and Proteins With Through Heteroatom-and Metal-[ 18 F]fluoridementioning
confidence: 99%
“…[88] Recently,n ew chelators for the formation of 18 F À Al complexes were developed by Bormans and co-workers to address heatsensitive biomolecules.T he new acyclicp olydentate ligands were less rigid than macrocyclic NOTA,w hich substantially reduced the activation energy for AlÀFcomplexation. [194][195][196] Fore xample,[ 18 F]GaF 3 (BnMe 2 -tacn) could be obtained by 19 F/ 18 F exchange in high RCY (81 AE 1%;Scheme 33 D). [192,193] Recently Reid and co-workers developed ac helating strategy for the preparation of as eries of 18 F-labeled Ga compounds through halogen- 18 Fe xchange.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…91,92 However, 18 F/ 19 F isotope exchange of [ 18 F]trifluoroborates can be carried out at room temperature at pH 2–3 to produce many 18 F-labeled radiopharmaceuticals with high specific activity. 93–97 Lewis acid–base Al 18 F-complex labeling has also been developed to produce a variety of 18 F-labeled radiopharmaceuticals via coordination of Al 3+ and chelators. Particularly, triazacyclononanes derivatives such as NOTA are commonly used as a chelator to form {Al 18 F} 2+ generating radiotracers.…”
Section: Introductionmentioning
confidence: 99%